Determination of Imatinib and CGP74588 in Rat Plasma by HPLC and Its Application to a Pharmacokinetic Study - Lin, Jiamiao; Ying, Na; Wu, Yanli; Lin, Gaotong (Current Pharmaceutical Analysis, 2018)
Objective: A simple, reliable and specific method of HPLC which was performed on a reversed- phase Agilent SB column was developed for the determination of imatinib and CGP74588. Method: The mobile phase comprised water-acetonitrile-0.1% trifluoroacetic acid (59:21:20, v/v/v) flowed at the rate of 1 mL/min at 40°C. The detection wavelength was 278nm. Results: Sensitivity has been illustrated in this method, and a good linear relationship was observed between 0.1-20.00 μg/mL for imatinib with r2=0.9994 and 0.01-2.00 μg/mL for CGP74588 with r2=0.9998 in rat plasma. The relative recoveries of imatinib and CGP74588 were all more than 93%, whilst the absolute recoveries of imatinib and CGP74588 were all more than 75%. Both intra- and inter-day precisions were all less than 4.5% for imatinib and 4.74% for GCP74588. The limits of quantification of these analytic methods were 0.1 μg/mL for imatinib and 0.01 μg/mL for CGP74588. Conclusion: The method was suitable for studying the pharmacokinetic parameters of imatinib and GCP74588 and routine analysis.
Keywords: N-desmethyl imatinib